2016
DOI: 10.1074/jbc.m116.737593
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor-interacting Protein-like 1 Is an Obligate Chaperone of Phosphodiesterase 6 and Is Assisted by the γ-Subunit of Its Client

Abstract: Phosphodiesterase 6 (PDE6) is the effector enzyme in the phototransduction cascade and is critical for the health of both rod and cone photoreceptors. Its dysfunction, caused by mutations in either the enzyme itself or AIPL1 (aryl hydrocarbon receptor-interacting protein-like 1), leads to retinal diseases culminating in blindness. Progress in research on PDE6 and AIPL1 has been severely hampered by failure to express functional PDE6 in a heterologous expression system. Here, we demonstrated that AIPL1 is an ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 58 publications
(60 reference statements)
3
78
0
Order By: Relevance
“…In lysates of HEK293T cells cotransfected with PDE6C and Pγ, cGMP hydrolysis did not exceed the very low levels in lysates from untransfected cells (7.6 ± 2.7 pmol cGMP hydrolyzed per milligram protein per minute). Consistent with previous observations (22), coexpression of PDE6C and Pγ with WT AIPL1 led to robust cGMP hydrolysis in cell lysates (14.7 ± 1. in transfected HEK293T cells were similar to those of the wildtype AIPL1 (SI Appendix, Fig. S10).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…In lysates of HEK293T cells cotransfected with PDE6C and Pγ, cGMP hydrolysis did not exceed the very low levels in lysates from untransfected cells (7.6 ± 2.7 pmol cGMP hydrolyzed per milligram protein per minute). Consistent with previous observations (22), coexpression of PDE6C and Pγ with WT AIPL1 led to robust cGMP hydrolysis in cell lysates (14.7 ± 1. in transfected HEK293T cells were similar to those of the wildtype AIPL1 (SI Appendix, Fig. S10).…”
Section: Resultssupporting
confidence: 79%
“…Recently, we confirmed that three AIPL1 mutations linked to LCA (V71F, W72S, and C89R) are pathogenic, by demonstrating that they fail to chaperone PDE6 in HEK293T cells (22). W72S and C89R formed perinuclear aggregates, an outcome consistent with protein instability.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations